Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
see explanation
Step-by-step explanation:
(1)
The common ratio r of a geometric sequence is
r = [tex]\frac{a_{2} }{x_{1} }[/tex] = [tex]\frac{a_{3} }{a_{2} }[/tex] , so
[tex]\frac{x+1}{x-1}[/tex] = [tex]\frac{x}{x+1}[/tex] ( cross- multiply )
(x + 1)² = x(x - 1) ← expand both sides
x² + 2x + 1 = x² - x ( subtract x² - x from both sides )
3x + 1 = 0 ( subtract 1 from both sides )
3x = - 1 ( divide both sides by 3 )
x = - [tex]\frac{1}{3}[/tex]
(2)
r = [tex]\frac{x}{x+1}[/tex] = [tex]\frac{-\frac{1}{3} }{-\frac{1}{3}+1 }[/tex] = [tex]\frac{-\frac{1}{3} }{\frac{2}{3} }[/tex] = - [tex]\frac{1}{2}[/tex]
(3)
If - 1 < r < 1 then the sequence will converge
r = - [tex]\frac{1}{2}[/tex] meets this criteria , thus the sequence is convergent
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.